2015
DOI: 10.1111/cei.12691
|View full text |Cite
|
Sign up to set email alerts
|

Preventative role of interleukin-17 producing regulatory T helper type 17 (Treg17) cells in type 1 diabetes in non-obese diabetic mice

Abstract: 1 S. M. B. and E. N. contributed equally to this work. SummaryT helper type 17 (Th17) cells have been shown to be pathogenic in autoimmune diseases; however, their role in type 1 diabetes (T1D) remains inconclusive. We have found that Th17 differentiation of CD4 1 T cells from BDC2Á5 T cell receptor transgenic non-obese diabetic (NOD) mice can be driven by interleukin (IL)-23 1 IL-6 to produce large amounts of IL-22, and these cells induce T1D in young NOD mice upon adoptive transfer. Conversely, polarizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 31 publications
(58 reference statements)
0
42
0
1
Order By: Relevance
“…Recent findings suggest that in certain conditions, IL‐17 may have anti‐inflammatory actions . In experimental autoimmune uveitis in rats, IL‐17 inhibition was pro‐inflammatory and aggravated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that in certain conditions, IL‐17 may have anti‐inflammatory actions . In experimental autoimmune uveitis in rats, IL‐17 inhibition was pro‐inflammatory and aggravated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Th22 cells are present mainly in skin or anatomical barriers . In addition, AhR is the transcription factor for the polarization of CD4 + T cells into Th22 cells , and we showed previously that polarization of pathogenic Th17 cells by IL‐23 plus IL‐6 down‐regulated AhR expression . Therefore, the cells producing both IL‐22 and IFN‐γ are of Th17 lineage.…”
Section: Discussionmentioning
confidence: 88%
“…We found that the expression of aryl hydrocarbon receptor (AhR) did not change significantly in these cells. We have shown previously that pathogenic Th17 cells induced by IL-23 1 IL-6 express little AhR [3]. Conversely, the IL-10 level was significantly lower in the diabetic group versus the non-diabetic NOD mice supporting the down-regulation of regulatory T cells (T reg ) upon disease progression (P < 0Á05).…”
Section: Il-22-producing Th17 Cells In Diabetic Nod Micementioning
confidence: 86%
See 2 more Smart Citations